Factors Associated With Chemical Safety Status In Small And Medium Printing Enterprises In Penang - Yon, Hazlina (2007)

(untitled)
Satu kajian berkenaan status keselamatan kimia bagi syarikat keeil dan sederhana telah dijalankan dalam tahun 2005 sehingga tahun 2006. Borang kajisefidik telah diagihkan kepada 254 buah syarikat percetakan tetapi hanya 122 keping borang sahaja yang telah diisi dan dikembalikan kepada penyelidik. Kajiselidik tersebut bertujuan untuk mengenalpasti faktor-faktor yang berkaitan dengan status keselamatan kimia di syarikat-syarikat kecil dan sederhana dengan mengukur tahap pengetahuan dan tahap kesedaran mengenai keselamatan kimia ke atas orang yang bertanggungjawab terhadap keselamatal) dan kesihatan pekerjaan di sesebuah tempat kerja. A study on the status of chemical safety of small medium enterprises SMEs ~as conducted in 2005 to 2006. Surveys forms were distributed to 254 enterprises but Inly 122 forms were filled and returned. The survey was aimed to determine factors lssociated with the chemical safety status in those enterprises by measuring the :nowledge and level of awareness towards chemical safety of the person responsible or occupational safety and health (OSH) at the respective workplaces. Establishment )f safe working procedures, establishment of monitoring of workers exposure )rogramme and medical surveillance programme, participation of workers and ~stablishment of process hazard identification, establishment of chemical safety data ,heets and establishment of operational control methods at work were found to be issociated with the chemical safety status in small medium enterprises (SMEs).